ICT as an Enabler of Innovation. Evidence from German Microdata - Nadine Fabritz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2015)
Using data from a survey of German manufacturing firms, this paper empirically tests the hypothesis that investment in ICT enables product innovation at the firm level. The empirical approach employs a value-added model, which controls for time-invariant firm characteristics. We instrument with exogenous impulses that affect firms decision to invest in ICT to account for remaining endogeneity that arises due to the fact that firms may decide to innovate and invest in ICT simultaneously. In addition, we employ matching methods to corroborate the results. We find consistent evidence that ICT investment increases firms product innovations.
Keywords: O14; O31; 330; Innovation; information and communication technology; manufacturing sector